Modeling and simulation of packet scheduling in the downlink long term evolution system - Mohd. Ramli, Huda Adibah; Sandrasegaran, Kumbesan; Basukala, Riyaj; Wu, Leijia (Institute of Electrical and Electronics Engineers Inc., 2009)
Long term evolution (LTE) is the next generation wireless system that uses orthogonal frequency division multiple access (OFDMA) technology in the downlink. Packet scheduling becomes paramount as the wireless systems are moving towards all IP transmissions. Since LTE system is relatively new, very little work has been published to date that can precisely model and simulate the downlink LTE system environment. This paper provides detailed descriptions on modeling and simulation of packet scheduling in the downlink LTE system using a C++ simulation tool. The tool accurately modeled the wireless system parameters and can be used for study of optimization of the LTE system.